The influence of probing-prompting learning model toward students’ mathematical reflective thinking skills - Luthvia Zahra; Bambang Sri Anggoro; Tommy Tanu Wijaya; Santi Widyawati (Journal of Advanced Sciences and Mathematics Education, 2021)
This research was conducted at SMP Negeri 32 Bandar Lampung to determine the influence of the Probing-Prompting learning model toward students' mathematical reflective thinking skills on the relations and functions learning materials. The researchers employed the quasi-experimental design. The research data was collected through a description test. This research was conducted on the eighth-grade students of SMP Negeri 32 Bandar Lampung. The samples consisted of sixty students determined using the cluster random sampling technique. Based on the Two-Way ANOVA test, the Probing-Prompting learning model significantly affected students' mathematical reflective thinking. Therefore, the learning model influenced the students' mathematical reflective thinking skills on the relations and functions learning materials.